Electrochemical nanobiosensors perspectives for COVID 19 pandemic - Rajshri Kundlik Satvekar (International Association of Physical Chemists (IAPC), 2021)
Early, rapid and ultrasensitive diagnosis of COVID-19 to facilitate high-throughput analysis without a high degree of technical expertise or sophisticated equipment is necessary to expand COVID-19 testing capability. Leveraging interdisciplinary proficiency in analytical chemistry, biomedical instrumentation, molecular biology, microfluidics, and nanotechnology, considerable advances have been made to develop a novel diagnostic tool that assures superior key performances for COVID-19 diagnosis. This review summarizes the nano-enabled systems such as electrochemical nanobiosensor for SARS-CoV-2 virus detection and emphasizes promising diagnostic techniques to extensively facilitate the diagnostic practices during the COVID-19 pandemic. Currently, three main diagnostic methods have been widely used in the COVID-19 pandemic: nucleic acid (NA)-based testing, computed tomography (CT), and serological testing. NA-based detection of SARS-CoV-2 such as Reverse transcription polymerase chain reaction has become the gold standard for COVID-19 diagnosis. This review congregates significant contributions in the electrochemical nanobiosensor research area, which is helpful for further nanobiosensor development. Although many efforts were taken to detect the SARS-CoV-2, the COVID 19 diagnosis still relies on expensive prolonged analysis. A rapid and reliable alternative is the utilization of a low-cost nanobiosensor for SARS-CoV-2 detection that can rapidly diagnose the disease even in asymptomatic conditions with high reliability and sensitivity.